RED GRAM PRODUCTIVITY ENHANCEMENT THROUGH FRONT LINE DEMONSTRATIONS IN PRAKASAM DISTRICT OF ANDHRA PRADESH - G.V. SUNEEL KUMAR, O. SARADA and (The Journal of Research, PJTSAU, 2019)
The present investigation was carried out in Prakasam District of Andhra Pradesh during the year 2014-15. Thirty Front Line Demonstrations were conducted during 2013-14 in Kharif season in three villages (Cumbum, Bestavaripeta and Pusalapadu) of 3 major redgram growing mandals. Demonstrations were organized in 12 hectares under redgram with best management practices using high yielding variety LRG 41. Ninety farmers participated in redgram demonstrations (10 demonstration farmers and 20 other farmers from each village) were purposively selected for the study. The results of demonstrations showed that farmers could increase the redgram productivity notably by switching over to improved variety and adoption of improved production technology. There was an yield increase of 26.67 per cent, decreased cost of cultivation of 30.77 per cent and increased net returns of 38.86 per cent in demonstration plots over control plots. The average CB ratio recorded in demo units was 1: 3.7 over 1:1.25 in farmers practice. Regarding the effect of FLDs on adoption of demonstrated practices almost sixty per cent (56.67%) of the farmers not adopted recommended High Yielding Variety before conducting demonstrations whereas more than eighty per cent of them have adopted LRG 41 variety after demonstration. With respect to seed treatment great majority (91.11%) have not adopted seed treatment, but after realizing the benefit almost seventy seven per cent of them were adopting seed treatment. Cent per cent of the farmers were not using neem oil as a prophylactic spray previously but sixty one per cent of them were adopting neem oil spray as prophylactic against Maruka after participating in demonstrations. Regarding need based pest and disease management, eighty four per cent of the farmers were going for indiscriminate sprays before organizing demonstrations, but sixty eight per cent of them switched over to need based sprays after noticing the results in demonstrated plots. Majority of the redgram farmers expressed production constraints like flower drop due to continuous dry spell (87.77%), poor seed quality supplied by Govt. agencies (84.44%), severe incidence of Maruca and pod fly (80.00%), increased cost of cultivation (73.33%), severe wilt problem (58.88%) and non availability of drought tolerant varieties (51.11%)